Bioactive Contents, BSLT Toxicity and antioxidants from Apis dorsata Binghami and Apis mellifera nest extracts - Tuegeh, Reinny Silvana; Sumampouw, Herry Maurits; Tanor, Meity Neltje; Mokosuli, Yermia Semuel (Fakultas Keguruan dan Ilmu Pendidikan Universitas Labuhanbatu, 2023)
Beenest is rich in secondary metabolites because honeycombs, among others, are formed from plant resins (propolis). This study aimed to analyze differences in flavonoid content and in vitro antioxidant activity of Apis dorsata Binghami and Apis mellifera nest extracts. The samples used were A. dorsata from North Sulawesi and A. mellifera from South Sulawesi. The honeycomb was extracted using 95% ethanol solvent. Honeycomb extract was analyzed for its flavonoid content by the HPLC method, toxicity was tested by the BSLT method, and in vitro antioxidant activity was tested by the DPPH method. The results of the analysis of flavonoids showed that A. dorsata nest extract produced 21 types of compounds while A. mellifera produced 26 types of compounds. The toxicity test results showed that the A. dorsata nest extract had a better LC50 of 245,691 mg/l than the A. mellifera nest extract with an LC50 of 443,701 mg/l. The in vitro antioxidant test results of A. dorsata nest extract were more robust, namely IC 50 1.161 mg/l, compared to A. mellifera nest extract IC 50 2.404 mg/l. However, both were included in the category of powerful antioxidants. In vitro, anticancer test results on MCF-7 cells, A. mellifera nest extract was active with IC 50 100.02mg/l. Compared to A. dorsata extract, it was active with IC 50 102.217mg/l, but the two were not significantly different. Based on the analysis of flavonoid content, toxicity test, and antioxidant test, A.dorsata and A.mellifera honeycomb extracts have potential as in vitro antioxidants